Vitamin D in clinical medicine - Giustina, Andrea 1962-; Bilezikian, John P. (Frontiers of hormone research / series editor Ezio Ghigo, 2018)
Vitamin D deficiency is prevalent today not only among the elderly but pervasively throughout all ages of life. This is due, in part, to systemic diseases that affect vitamin D metabolism, to changes in lifestyle, such as insufficient exposure to sunlight, and to increased use of sunscreen. Apart from the obvious effects of vitamin D deficiency on skeletal metabolism, the problem is assuming even greater significance because observational and interventional studies have linked vitamin D deficiency to cardiovascular disease, cancer, and diabetes. This book addresses a variety of important issues that have emerged from this fast-moving area of clinical medicine. The topics include assays of vitamin D and its binding protein, effects on aging and associated complications, primary and secondary states of altered parathyroid hormone secretion, vitamin D in the growing years of children and adolescents, nutritional requirements, and vitamin D as it relates to systemic disorders such as diabetes mellitus. Vitamin D in Clinical Medicine aims to offer new insights, in an evidence-based way, on important issues related to vitamin D. It is written for general practitioners and internists, as well as for endocrinologists, nutritionists, pulmonologists, cardiologists, and oncologists.